Anti-Parkinson Drug from Chemical Medicines and Herbal Medicines: A Review - Yeni Yeni; Xia Wu; Budi Arman (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2021)
Parkinson's disease (PD) is a disease of the central nervous system. It is a progressive disorder, meaning it gets worse over time. PD usually characterized by tremor, rigidity, akinesia and postural autonomic instability. In addition, it may also cause a series of non-motor symptoms (NMSs). This disease affects a small area of cells in the middle of the brain. This area is called the substantia nigra (SNc). The cells slowly lose their ability to produce a chemical called dopamine. The disease usually appears in the age over 60 years. Nowadays, a lot of anti-Parkinson drugs have been found either from that of chemicals or herbs. In this essay anti-Parkinson drugs from chemical medicine and herbal medicines especially from china will be discussed. Anti-Parkinson's drugs are derived from chemical medicines include levodopa (l-dopa), dopamine agonists, MAO-B inhibitors, catechol O-methyltransferase (COMT) inhibitors, anticholinergics and amantadine. Meanwhile, anti-Parkinson drugs derived from herbal medicine include Scutellaria baicalensis Georgi, Polygonum cuspidatum Sieb. et Zucc., green tea (Camellia sinensis L.), Panax ginseng C. A. Mey., Cistanche deserticola Y. C. Ma, Panax Notoginseng Wall. var notoginseng (Burkill.) F.H. Chen, Gastrodia elata Blume and Polygala tenuifoliaWilld.. These drugs have the same effects to help ease symptoms of Parkinson’s and can increase the amount of dopamine in substantia nigra pars compacta (SNc). However, some chemical drugs have more side effects although herbal medicines are less clear,  more tests need to be planned.